Effect of early childhood malnutrition on tooth eruption in Haitian adolescents - Psoter W, Gebrian B, Prophete S, Reid B, Katz R. (Journal compilation, 2008)
Effect of early childhood malnutrition on tooth eruption in Haitian adolescents